Bu-Fei-Huo-Xue capsule alleviates bleomycin-induced pulmonary fibrosis in mice through modulating gut microbiota - Hu, Haibo; Wang, Fengchan; Han, Ping; Li, Peng; Wang, Kun; Song, Huan; Zhao, Guojing; Li, Yue; Lu, Xuechao; Tao, Weihong; Cui, Huantian (Frontiers in Pharmacology, 2023)
Bu-Fei-Huo-Xue capsule (BFHX) has been used to treat pulmonary fibrosis (PF) in clinic. However, the mechanism of BFHX on PF remains unclear. Recent studies have shown that the changes in gut microbiota were closely related to the progression of PF. Modulating gut microbiota provides new thoughts in the treatment of PF. In this study, a mouse model of PF was induced using bleomycin (BLM) and treated with BFHX. We firstly evaluated the therapeutic effects of BFHX on PF model mice. Besides, the anti-inflammatory and anti-oxidative effects of BFHX were evaluated. Furthermore, 16S rRNA sequencing was used to observe the changes in gut microbiota in PF model mice after BFHX treatment. Our results showed that BFHX significantly reduced the collagen deposition in PF model mice. BFHX treatment also reduced the levels of pro-inflammatory cytokines and inhibited the oxidative stress in lung. 16S rRNA sequencing showed that BFHX affected the diversity of gut microbiota and the relative abundances of gut microbiota such as Lactobacillus，Lachnospiraceae_NK4A136_group，and Romboutsia. In conclusion, our study demonstrated the therapeutic effects of BFHX on PF. The mechanisms of BFHX on PF may be associated with regulating gut microbiota.